Determination of Somatotypes of Children With Adolescent Idiopathic Scoliosis and Its Relationship With Scoliosis - APTİ, ADNAN; Çolak, Tuğba Kuru; Akçay, Burçin; Çolak, İlker (Bayrakol Medical Publisher, 2023)
Aim: Adolescent idiopathic scoliosis (AIS) is a three-dimensional deformity of the spine. In adolescence, body morphology can change for various reasons such as genetics, nutrition, and level of physical activity. It has been reported that there are differences in the normal physical growth pattern in children with AIS, which may be due to hormonal changes. The relationship between body morphology and scoliosis is questionable because of the differences that scoliosis creates in the spinal structure. The aim of this study was to define the somatotype characteristics of children with AIS and compare the somatotypes with healthy, age and sex-matched controls.Material and Methods: A retrospective evaluation was performed on 38 children with AIS and 27 age-matched healthy control subjects. Cobb angles and angle of trunk rotation (ATR) values were used to determine scoliosis and trunk gibbosity. Cobb angles were measured on standing anterior-posterior radiographs and the ATR using Adam's forward bending test with a scoliometer. Somatotypes were defined according to the Heath-Carter method and body morphology was categorized into three different components: endomorphy, mesomorphy, and ectomorphy.Results: Ectomorphy was the dominant type in the AIS group, and endomorphy was the dominant type in the control group. The endomorphic somatotype in individuals with scoliosis was determined at a statistically significantly lower rate than in the control group (p=0.048). There was a moderate negative correlation (p=0.001, r=-0.466) between the Cobb angle and the values of the endomorphy component, and between the ATR and the endomorphy values (p=0.010, r=-0.318).Discussion: The lower rate of endomorphic somatotype was an evident difference in children with scoliosis. These differences may cause problems in the growth and development of the spine and the skeletal structures attached to the spine during adolescence when rapid growth and development occur. Whether this difference is related to nutrition, genetic and hormonal factors, or psychosocial factors remains to be determined.
Keywords: Somatotype; Scoliosis; Adolescents; Human Body Morphology